Islam dan Kebangsaan : Studi tentang Politik Islam masa Pergerakan Nasional di Indonesia - Nasihin Nasihin (Universitas Islam Negeri Alauddin Makassar, 2014)
This paper describes the political Islam that is applied by the Dutch government during the National Movement and its implications to the formation of the State of Indonesia. As a government policy, political Islam is precisely be the trigger for a variety of organizations labeled Islam to realize itself as an entity of Muslims and as people bumiputera. Principal important issues raised in this paper is how Islam can become binding nationality bumiputera people in Indonesia?. Re related to social phenomena of all Islamic, from time to time, in principle, does not shift to the issue of the integrity of the Ummah and the